Predictors of the dependence on smartphones: The neglect of studies among Muslim students - Christine Tan, Nya-Ling; Muhammad Ashraf, Fauzi; Ojo, Adedapo Oluwaseyi (Emerald Insight, 2022)
Purpose: This study aims to posit the extended version of the technology acceptance model to explain the psychological factors of Muslim university students’ smartphone addictive behaviour and neglect of studies. In particular, this research conceptualised addictive behaviour as smartphone dependency and proposed process usage, flow, habitual smartphone behaviour and preference for online social interaction (POSI) as the associated factors. Besides, this study investigated the effect of smartphone dependency on the neglect of studies. Design/methodology/approach: Following the quantitative research design, this research tested the proposed model using data collected from Muslim students’ smartphone users in Malaysia. The analyses were based on the partial least squares–structural equation modelling technique. Findings: The results revealed that flow has the most significant influence on smartphone dependency. Habitual behaviour and process usage were also significant predictors, but POSI was not significantly associated with smartphone dependency. Also, smartphone dependency was significantly related to the neglect of studies. Research limitations/implications: This study provides empirical support to guide university management in preventing Muslim students’ over-dependence on smartphones. The Muslim community is synonymous with time management, where overdependence would diminish students’ religious and academic responsibilities. Such overdependence can cause neglect of studies; thus, the research findings can assist the university in introducing policies and campaigns that can educate students on the negative consequences of this pervasive digital addiction and ways to overcome them. This study contributes to the body of knowledge in understanding Muslim students coping mechanisms through smartphone usage. Originality/value: This study contributes to the literature by demonstrating the psychological factors of smartphone addiction and the resultant effect on the neglect of studies among Muslim university students.